Analysis on Mechanical Properties of Waste High Density Polyethylene (HDPE) Plastic - Yusa’, Nur Atikah (IRC, 2020)
High Density Polyethylene (HDPE) has been widely used in industrial and commercial products nowadays because of its material. HDPE has outstanding tensile strength and it also has high-impact resistance and melting point. There is no doubt plastic is very useful. Despite that, the problem from plastic is that most of it is not biodegradable and it takes hundred years to rot. This study aim to reduce solid waste from HDPE plastic by using recycling and reuse method and could save resources and raw material for future generations. The objective of this research is to analyse and compare the mechanical properties of HDPE waste and compare it with standard HDPE. Nonetheless, there is still not much analysis of the mechanical properties of recycled HDPE as there is not much information on the materials. This study provides evidence of lower mechanical properties of recycled HDPE compared to pure HDPE by using tensile and hardness test. Hence, all findings suggest that recycled HDPE to add another fiber to strengthen its bonding.